ANALISIS PROSES PEMBELAJARAN MATEMATIKA DI KELAS VIII AKSELERASI SMP NEGERI 1 BOYOLALI - Nurmalitasari, Nurmalitasari; Sujadi, Imam; Kusmayadi, Tri Atmojo (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aim of the research was to describe planning and implementation of the learning process performed by mathematics teacher in the class VIII acceleration of SMPN 1 Boyolali. It was a qualitative research casestudy.The subject of this research were taken by using the purposive sampling. The subject of the research were mathematics teacher class VIII acceleration fisrt grade and second grade. The techniques of collecting the data in this research were documentation, interview and observation. The techniques of validating the data were source triangulation and time triangulation. The technique of analyzing the data was Miles and Huberman concept, namely, data reduction, data presentation, and conclusion drawing. The findings of the research show that planning of the learning process performed mathematics teacher in the class VIII acceleration of SMPN 1 Boyolali equal to the planning process of mathematics learning in the regular classroom, the difference lies in the allocation of time. The process of preparation of instructional time allocation in accelerated classes every basic competence with respect to the number of weeks was effective as seen from accelerated academic calendar, the number of basic competencies, depth, complexity, and level of interest of a basic competence. Implementation of the learning process performed mathematics teacher in the class VIII acceleration of SMPN 1 Boyolali, approaches, strategiesandmethods, is student-oriented activities. The approachused by teachersis the approach behaviour (behaviour therapy). Learning strategies are instructional strategies that emphasize learning out comes in intellectual abilities and learning strategies student-oriented activities. The method is applied teacher combines several methods such as lectures, question and answer, discussion and drill that emphasize student activity. Keywords: planning of the learning process, implementation of the learning process, syllabus, lesson plan, learning approaches, learning strategies,Â learning methods, acceleration